Koncepcja dzielnej ofiary a obszary kulturowo-prawnej dyskryminacji instytucjonalnej kobiet w Polsce - Kaptur, Klaudia M. (Studia Prawa Publicznego, 2023)
Institutional discrimination against women in Poland is a social problem that persists despite constitutional guarantees of gender equality and legislation providing for compensatory measures. The article analyzes the possibility of using M. Marody’s concept of the “brave victim” as a means of designing compensatory actions in legislation and enforcement that will help eliminate institutional discrimination. Institutional discrimination is defined in legal doctrine as discrimination that occurs at the level of a given institution, organization, or even society as a whole. The article also analyzes cultural and social factors that condition or contribute to the deepening of legal and social inequality for women. The article identifies areas of institutional discrimination in Poland, including: the labor market, parental rights, social rights, access to political functions, and increasing women’s participation in public life. The analysis of national legal regulations and regulations implemented from EU law indicates the heterogeneity of protection against discrimination. The article proposes conditions and principles for the application of special legal solutions that establish anti-discrimination standards applicable in the current social conditions in Poland. The concept of the “brave victim” is a social fact that the legislator should take into account when designing policy law to avoid social tensions and develop effective legal solutions to counter discrimination.